The Application of Awareness Training to Increase Self-Confidence in Young Athletes - Qonita Dian Parahita; Miftakhul Jannah (Universitas Negeri Surabaya, 2023)
The purpose of this research is to describe the application of awareness training to increase the self-confidence of young athletes. Self-confidence supports the formation of training commitments, skills development, involvement in competition, and potential physical abilities for future sports. Using a quantitative experimental method, with a quasi experimental design, and pretest-posttest control group design. Sampling used saturated sampling with a population of 24 young DBON athletes. Using the Kolmogorov Smirnov normality test. Using the paired t-test hypothesis test and gain score. The results of the paired t-test showed that the significance value of the pre-test and post-test pairs of the experimental group was 0.000, which means that there was a significant difference in average. The gain score test results showed an increase in the experimental group 8.17, while in the control group 1.83. The application of awareness training is effective in increasing the self-confidence of young athletes. The significant increase in the self-confidence of young athletes after awareness training can be seen from the significant difference in the mean between the pre-test and post-test in the experimental group. This shows that awareness training has the potential to increase self-confidence and provide benefits for coaching young athletes.